Magma storage conditions beneath Krakatau, Indonesia: insight from geochemistry and rock magnetism studies - Pratama, Aditya; Nurfiani, Dini; Suryanata, Putu Billy; Ismail, Taufik; Bunga Naen, Gabriela Nogo Retnaningtyas; Abdurrachman, Mirzam; Supriyadi Banggur, Wilfridus Ferdinando; Asri, Nining Sumawati; Nareswari, Ratika Benita; Bijaksana, Satria; Hanif, Muhammad; Kriswati, Estu; et al. (Frontiers in Earth Science, 2023)
Understanding the evolution of magma storage conditions on volcanoes which have had more than one caldera-forming eruption (CFE) is important to know about past and present conditions, as a key to forecast future potential hazards. Krakatau volcano is characterized by cyclic phases of growth and destruction of the edifice. A volcanostratigraphic study identified three eruptive periods: Old Krakatau, Young Krakatau, and Anak Krakatau. The Old and Young Krakatau periods ended with the first and second CFE respectively. Due to its permanent activity and edifice evolution, Krakatau poses a high risk on the surrounding inhabited islands. In this study, we combined geochemistry, rock magnetic, and petrology to infer the evolution of magma storage conditions from Old to Anak Krakatau periods. This study is the first to report on the chemical and rock magnetic characteristics, as well as storage system conditions of Old Krakatau and its relation to the ongoing evolution of Krakatau. Our data show that: 1) Old and Young Krakatau magma storage regions are shallow (within the upper 3 km), contain more differentiated magmas, from which the Old Krakatau magmas may be less oxidized and had lower temperatures than Young Krakatau; 2) Anak Krakatau magma storage is deeper (up to 26 km), less differentiated, and erupted hotter but more reduced compared to Old and Young Krakatau. The Old and Young Krakatau lavas were the products of pre-CFE and their chemical characteristics are included at maturation phase, whereas the Young Krakatau pumice samples were the product of the second CFE. Lastly, the post-second CFE activity of AK is currently in an incubation phase and represented by mafic products of frequent and small eruptions. Knowing that the volcano has experienced maturation and CFE phases in the past, the current AK may evolve to those phases in the future.